A Sociolinguistic Analysis of Slang Words Found in “The Mitchells VS The Machines” Movie - Rahman, Muhammad Fathur; Zaim, M. (Universitas Negeri Padang, 2023)
This study aims to find out the contextual meaning of slang words and the functions of slang words used in the movie The Mitchells vs the Machines. Then, in this study the researcher used a descriptive method. The Mitchells vs the Machines movie was selected as data from the study using Holmes and Zou & Fan's theory. The researcher found 32 slang words spoken by Katie which were then categorized based on the type of 19 newly made slang words and 13 slang words from newly interpreted slang words. Slang words are all analyzed. Contextual meaning is determined based on social factors involving the participants' social relations, the setting of the place, and the topic of conversation. Then, the researcher examines the function of slang for each slang word that has been analysed. As a result, the researcher found 2 types of Function of slang in this movie, namely, PSI (Pursuit-Self Identity) and EF (Emotive Feeling).